Correlation of Lateral Pinch Strength with Hand Span in Bead Embroiderers - Irin Parven; Satabdi Ghosh; Segupta Kiswara; Rehana Parveen; Zeenatul Momena (KYAMC Journal, 2023)
Background: Lateral pinch strength is a commonly employed indices of strength used in hand evaluations. For all handicrafts professionals, grip and pinch strength is an important criterion to be successful in their profession. The bead embroiderers are one of the major handicrafts worker groups of Bangladesh. Objectives: The study was planned to compare and correlate hand span and lateral pinch strength of the hand in bead embroiderers to establish baseline data of our own for further studies. Materials and Methods: There was a cross-sectional and analytical study conducted on 150 bead embroiderers in group B and 50 sedentary workers in group A, carried out in the Department of Anatomy, Dhaka Medical College, Dhaka between July 2016 and July 2017. The lateral pinch was measured by using a Pinch Gauge Dynamometer. The hand span was taken by using a ruler and unpaired student’s t-test and Pearson’s correlation coefficient were done to compare and correlate. Results: Lateral pinch strength showed a significant positive correlation with hand span in group B (r = +0.234, P<0.01) and non-significant positive correlation with hand span in group A (r = +0.275, P=0.053). Conclusion: The study findings may contribute significantly to current knowledge for designing machines and handheld devices. KYAMC Journal Vol. 14, No. 02, July 2023: 92-95.